2022
DOI: 10.7326/m22-2116
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Improvements in COVID-19 Outcomes for Hospitalized Adults: A Post Hoc Observational Study of Remdesivir Group Participants in the Adaptive COVID-19 Treatment Trial

Abstract: Background:The COVID-19 standard of care (SOC) evolved rapidly during 2020 and 2021, but its cumulative effect over time is unclear.Objective: To evaluate whether recovery and mortality improved as SOC evolved, using data from ACTT (Adaptive .Design: ACTT is a series of phase 3, randomized, double-blind, placebo-controlled trials that evaluated COVID-19 therapeutics from February 2020 through May 2021. ACTT-1 compared remdesivir plus SOC to placebo plus SOC, and in ACTT-2 and ACTT-3, remdesivir plus SOC was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Our findings revealed that none of these substances exhibited any electrochemical activity. Furthermore, we also investigated the impact of 60-fold concentrations of inorganic ions such as Ca 2+ , Zn 2+ , Na + , Fe 3+ , K + , Mg 2+ , NO 3− , SO 4 2− , and Cl − , as well as substances like Mg stearate, Mannitol, microcrystalline cellulose, ferric oxide, titanium dioxide, poly(vinyl alcohol), lecithin, polyethylene glycol, and talc. Surprisingly, none of these substances had a discernible effect on the anodic current associated with BARI.…”
Section: Interference Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings revealed that none of these substances exhibited any electrochemical activity. Furthermore, we also investigated the impact of 60-fold concentrations of inorganic ions such as Ca 2+ , Zn 2+ , Na + , Fe 3+ , K + , Mg 2+ , NO 3− , SO 4 2− , and Cl − , as well as substances like Mg stearate, Mannitol, microcrystalline cellulose, ferric oxide, titanium dioxide, poly(vinyl alcohol), lecithin, polyethylene glycol, and talc. Surprisingly, none of these substances had a discernible effect on the anodic current associated with BARI.…”
Section: Interference Studiesmentioning
confidence: 99%
“…Its approval by the U.S. Food and Drug Administration (FDA) and the National Institutes of Health (NIH) represents a significant milestone in the ongoing battle against the pandemic. 3,4 In November 2020, the FDA granted emergency use authorization (EUA) for the utilization of Baricitinib (BARI) ([1-ethylsulfonyl-3-[4-(7H-pyrrolo [2,3-d]pyrimidin-4yl)pyrazol-1-yl]azetidin-3-yl]acetonitrile, depicted in Figure S1) in conjunction with remdesivir for the treatment of hospitalized COVID-19 patients. 5 This decision was based on promising clinical trial data, which demonstrated that the combination therapy significantly reduced recovery time and improved clinical outcomes compared to remdesivir alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in an incredibly short period of time, scientific research advances on prevention and treatment of SARS-CoV-2 infection were developed. The widespread rollout of SARS-CoV-2 vaccines and improvement in the standard of care in treatment has dramatically reduced morbidity and mortality of COVID-19 [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The disease of patients who are infected with SARS-CoV-2 progresses rapidly, and affected patients may get through acute respiratory distress syndrome (ARDS), 2 respiratory failure, 3 coagulopathies, 4 multiorgan dysfunction (MOD), 5 and even death within a short time. 6 To date, despite numerous kinds of treatments, such as Paxlovid, 7 Remdesivir, 8 dexamethasone, 9 convalescent plasma, 10 and vaccine, 11 have been tested among COVID-19 patients, the mortality among hospitalized patients remains high, especially among patients who admitted to the intensive care unit (ICU), with rates ranging from 35% to 66%. 3,[12][13][14][15] Because of the universal concerns about the virus and the disturbing nature of its accelerated spread, finding effective treatments has become a priority.…”
Section: Introductionmentioning
confidence: 99%